Advanced Nanomaterials in Biomedical, Sensor and Energy Applications - Chattopadhyay, Jayeeta; Srivastava, Rohit (Springer Singapore : Imprint: Springer, 2017)
This book is aimed at all those who are interested to understand the current research going on in nanomaterial science from the perspectives of biomedical, sensorial and energy applications including all aspects of physical chemist, chemical engineers and material scientist. Nanoscience and nanotechnology are at the forefront of modern research. The fast growing economy in this area requires experts with outstanding knowledge of nanoscience in combination with the skills to apply this knowledge in new products. A multidisciplinary scientific education is crucial to provide industry and research institutes with top quality experts who have a generic background in the different sub disciplines such as electronics, physics, chemistry, material science, biotechnology. The book covers recent advancement in nanoscience and nanotechnology particularly highlights the utilization of different types of nanomaterials in biomedical field, sensor and in the energy application. On the other hand, it leads the reader to the most significant recent developments in research. It provides a broad and in-depth coverage of the nanoscale materials and its depth significant applications. .
Keywords: Chemistry.; Energy harvesting.; Nanochemistry.; Biomedical engineering.; Nanotechnology.; elektronické knihy; electronic books